Cannabinoid CB2 receptors: Immunohistochemical localization in rat brain - Gong, Jian-Ping; Onaivi, Emmanuel S.; Ishiguro, Hiroki; Liu, Qing-Rong; Tagliaferro, Patricia A.; Brusco, Alicia; Uhl, George R. (Brain research, 2006)
Brain expression of CB2 cannabinoid receptors has been much less well established and characterized in comparison to the expression of brain CB1 receptors. Since CB2 receptors are intensely expressed in peripheral and immune tissues, expression in brain microglia has been anticipated. Nevertheless, we now describe expression of CB2-receptor-like immunoreactivity in brain in neuronal patterns that support broader CNS roles for this receptor. Two anti-CB2 affinity purified polyclonal antibodies were raised in rabbits immunized with peptide conjugates that corresponded to amino acids 1–33 and 20–33. Western blot analyses revealed specific bands that were identified using these sera and were absent when the sera were preadsorbed with 8.3 μg/ml of the immunizing peptides. These studies, and initial RT-PCR analyses of brain CB1 and CB2 mRNAs, also support the expression of brain CB2 receptor transcripts at levels much lower than those of CB1 receptors. CB2 cannabinoid receptor mRNA was clearly expressed in the cerebellum of wild type but not in CB2 knockout mice. CB2 immunostaining was detected in the interpolar part of spinal 5th nucleus of wild type but not in CB2 knockout mice, using a mouse C-terminal CB2 receptor antibody. Immunohistochemical analyses revealed abundant immunostaining for CB2 receptors in apparent neuronal and glial processes in a number of rat brain areas. Cerebellar Purkinje cells and hippocampal pyramidal cells revealed substantial immunoreactivity that was absent when sections were stained with preadsorbed sera. CB2 immunoreactivity was also observed in olfactory tubercle, islands of Calleja, cerebral cortex, striatum, thalamic nuclei, hippocampus, amygdala, substantia nigra, periaqueductal gray, paratrochlear nucleus, paralemniscal nucleus, red nucleus, pontine nuclei, inferior colliculus and the parvocellular portion of the medial vestibular nucleus. In-vitro, CB2 immunoreactivity was also present in hippocampal cell cultures. The multifocal expression of CB2 immunoreactivity in glial and neuronal patterns in a number of brain regions suggests reevaluation of the possible roles that CB2 receptors may play in the brain.